Surface science at the PEARL beamline of the Swiss Light Source. (21st December 2016) - Muntwiler, Matthias; Zhang, Jun; Stania, Roland; Matsui, Fumihiko; Oberta, Peter; Flechsig, Uwe; Patthey, Luc; Quitmann, Christoph; Glatzel, Thilo; Widmer, Roland; Meyer, Ernst; Jung, Thomas A.; et al.
Abstract : The Photo‐Emission and Atomic Resolution Laboratory is a new soft X‐ray beamline at the Swiss Light Source for the study of surface structure using photoelectron diffraction and scanning tunneling microscopy. Abstract : The Photo‐Emission and Atomic Resolution Laboratory (PEARL) is a new soft X‐ray beamline and surface science laboratory at the Swiss Light Source. PEARL is dedicated to the structural characterization of local bonding geometry at surfaces and interfaces of novel materials, in particular of molecular adsorbates, nanostructured surfaces, and surfaces of complex materials. The main experimental techniques are soft X‐ray photoelectron spectroscopy, photoelectron diffraction, and scanning tunneling microscopy (STM). Photoelectron diffraction in angle‐scanned mode measures bonding angles of atoms near the emitter atom, and thus allows the orientation of small molecules on a substrate to be determined. In energy scanned mode it measures the distance between the emitter and neighboring atoms; for example, between adsorbate and substrate. STM provides complementary, real‐space information, and is particularly useful for comparing the sample quality with reference measurements. In this article, the key features and measured performance data of the beamline and the experimental station are presented. As scientific examples, the adsorbate–substrate distance in hexagonal boron nitride on Ni(111), surface quantum well states in a metal‐organic network of dicyano‐anthracene on Cu(111), and circular dichroism in the photoelectron diffraction of Cu(111) are discussed.